Mia Mayhem is a superhero! - West, Kara (West, Kara. Mia Mayhem, 2018)
Eight-year-old Mia Macarooney is delighted to learn she is from a family of superheroes, but her acceptance into the Program for In Training Superheroes requires she take a placement exam.